2013
DOI: 10.1503/cjs.001012
|View full text |Cite
|
Sign up to set email alerts
|

High-concentration oxygen and surgical site infections in abdominal surgery: a meta-analysis

Abstract: Background: There has been recent interest in using high-concentration oxygen to prevent surgical site infections (SSIs). Previous meta-analyses in this area have produced conflicting results. With the publication of 2 new randomized controlled trials (RCTs) that were not included in previous meta-analyses, an updated review is warranted. Our objective was to perform a meta-analysis on RCTs comparing high-and low-concentration oxygen in adults undergoing open abdominal surgery. Methods:We completed independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
11
0
2
Order By: Relevance
“…In this study, our pooled results failed to demonstrate the advantage of supplemental inspired oxygen in reducing SSIs when all types of surgery were considered together. This finding was similar to the results of three published meta‐analyses . However, it should be noted that a significant heterogeneity was presented among all included RCTs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, our pooled results failed to demonstrate the advantage of supplemental inspired oxygen in reducing SSIs when all types of surgery were considered together. This finding was similar to the results of three published meta‐analyses . However, it should be noted that a significant heterogeneity was presented among all included RCTs.…”
Section: Discussionsupporting
confidence: 90%
“…After the elimination of 1917 irrelevant records, 29 citations remained and were retrieved for a more detailed evaluation. Of these, two non‐randomized studies , one non‐comparative study and nine meta‐analyses were excluded. Three studies with no SSI data were also excluded .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some previous meta‐analyses have shown no benefit of the supplemental inspired oxygen, these meta‐analyses included heterogeneous studies. The included studies differed especially in the type of surgical procedure, the diagnosis of SSIs and the technical skills of the surgeons …”
Section: Discussionmentioning
confidence: 99%
“…66,68,73,78,80 Despite these positive outcomes, the previous meta-analysis of Patel et al showed no evidence in reducing SSIs by the use of high inspired perioperative in abdominal surgery. 86 Also, in the meta-analysis of Klingel et al, no evidence is found that administration of high inspired oxygen would reduce the risk of SSIs in women undergoing cesarean section. 87 Schietroma et al investigated the effect of 80% inspired oxygen compared to 30% inspired oxygen perioperatively on the incidence of SSI in 81 patients undergoing elective colorectal surgery for rectal cancer.…”
Section: Supplemental Inspired Oxygenmentioning
confidence: 99%